To solve the expression, we will distribute the coefficients to the terms within the parentheses.
2(3x + 7) - 5(9x - 3)
= 2 * 3x + 2 * 7 - 5 * 9x + 5 * (-3)
= 6x + 14 - 45x - 15
Now, we can combine like terms.
= (6x - 45x) + (14 - 15)
= -39x - 1
Therefore, 2(3x + 7) - 5(9x - 3) simplifies to -39x - 1.
2(3x + 7) - 5(9x - 3)
11 answers
2(3x + 7) - (9x -3)
To solve the expression, we will distribute the coefficient of 2 to the terms within the parentheses.
2(3x + 7) - (9x - 3)
= 2 * 3x + 2 * 7 - (9x - 3)
= 6x + 14 - (9x - 3)
Now, we will distribute the negative sign to each term inside the second set of parentheses.
= 6x + 14 - 9x + 3
Now, we can combine like terms.
= (6x - 9x) + (14 + 3)
= -3x + 17
Therefore, 2(3x + 7) - (9x - 3) simplifies to -3x + 17.
2(3x + 7) - (9x - 3)
= 2 * 3x + 2 * 7 - (9x - 3)
= 6x + 14 - (9x - 3)
Now, we will distribute the negative sign to each term inside the second set of parentheses.
= 6x + 14 - 9x + 3
Now, we can combine like terms.
= (6x - 9x) + (14 + 3)
= -3x + 17
Therefore, 2(3x + 7) - (9x - 3) simplifies to -3x + 17.
(k + 1/3) + 10(1/2k - 1)
To solve the expression, we will apply the distributive property.
(k + 1/3) + 10(1/2k - 1)
= k + 1/3 + 10/2k - 10
= k + 1/3 + 5/2k - 10
To simplify further, we need a common denominator for the fractions involved. In this case, the least common denominator is 6k.
= (6k/k) + (2/k)(1/3) + 5(3/6k) - (60k/6k)
= (6k + 2)/(6k) + 5(3)/(6k) - (60k)/(6k)
= (6k + 2 + 15 - 60k)/(6k)
= (-54k + 17)/(6k)
Therefore, (k + 1/3) + 10(1/2k - 1) simplifies to (-54k + 17)/(6k).
(k + 1/3) + 10(1/2k - 1)
= k + 1/3 + 10/2k - 10
= k + 1/3 + 5/2k - 10
To simplify further, we need a common denominator for the fractions involved. In this case, the least common denominator is 6k.
= (6k/k) + (2/k)(1/3) + 5(3/6k) - (60k/6k)
= (6k + 2)/(6k) + 5(3)/(6k) - (60k)/(6k)
= (6k + 2 + 15 - 60k)/(6k)
= (-54k + 17)/(6k)
Therefore, (k + 1/3) + 10(1/2k - 1) simplifies to (-54k + 17)/(6k).
9(k + 1/3) + 10( 1/2k -1)
To solve the expression, we will apply the distributive property.
9(k + 1/3) + 10(1/2k - 1)
= 9k + 9(1/3) + 10/2k - 10
= 9k + 3/3 + 5/2k - 10
= 9k + 1 + 5/2k - 10
Next, we need to find a common denominator for the fractions involved. The least common denominator is 2k.
= (18k^2)/(2k) + (2)/(2k) + (5)/(2k) - (20k)/(2k)
= (18k^2 + 2 + 5 - 20k)/(2k)
= (18k^2 - 20k + 7)/(2k)
Therefore, 9(k + 1/3) + 10(1/2k - 1) simplifies to (18k^2 - 20k + 7)/(2k).
9(k + 1/3) + 10(1/2k - 1)
= 9k + 9(1/3) + 10/2k - 10
= 9k + 3/3 + 5/2k - 10
= 9k + 1 + 5/2k - 10
Next, we need to find a common denominator for the fractions involved. The least common denominator is 2k.
= (18k^2)/(2k) + (2)/(2k) + (5)/(2k) - (20k)/(2k)
= (18k^2 + 2 + 5 - 20k)/(2k)
= (18k^2 - 20k + 7)/(2k)
Therefore, 9(k + 1/3) + 10(1/2k - 1) simplifies to (18k^2 - 20k + 7)/(2k).
9k + 3 + 5k -10
To solve the expression, we will combine like terms.
9k + 3 + 5k -10
First, we will combine the terms with "k".
= 9k + 5k + 3 - 10
= 14k - 7
Therefore, 9k + 3 + 5k - 10 simplifies to 14k - 7.
9k + 3 + 5k -10
First, we will combine the terms with "k".
= 9k + 5k + 3 - 10
= 14k - 7
Therefore, 9k + 3 + 5k - 10 simplifies to 14k - 7.
4(g - 2) + (g + 2)
To solve the expression, we will distribute the coefficients to the terms within the parentheses.
4(g - 2) + (g + 2)
= 4g - 8 + g + 2
Now, we can combine like terms.
= 4g + g - 8 + 2
= 5g - 6
Therefore, 4(g - 2) + (g + 2) simplifies to 5g - 6.
4(g - 2) + (g + 2)
= 4g - 8 + g + 2
Now, we can combine like terms.
= 4g + g - 8 + 2
= 5g - 6
Therefore, 4(g - 2) + (g + 2) simplifies to 5g - 6.